Identification of Periodontal Pathogens in Atheromatous Plaques - Haraszthy, V.I.; Zambon, J.J.; Trevisan, M.; Zeid, M.; Genco, R.J. (Journal of periodontology (1970), 2000)
Background: Recent studies suggest that chronic infections including those associated with periodontitis increase the risk for coronary vascular disease (CVD) and stroke. We hypothesize that oral microorganisms including periodontal bacterial pathogens enter the blood stream during transient bacteremias where they may play a role in the development and progression of atherosclerosis leading to CVD. Methods: To test this hypothesis, 50 human specimens obtained during carotid endarterectomy were examined for the presence of Chlamydia pneumoniae, human cytomegalovirus, and bacterial 16S ribosomal RNA using specific oligonucleotide primers in polymerase chain reaction (PCR) assays. Approximately 100 ng of chromosomal DNA was extracted from each specimen and then amplified using standard conditions (30 cycles of 30 seconds at 95°C, 30 seconds at 55°C, and 30 seconds at 72°C). Bacterial 16S rDNA was amplified using 2 synthetic oligonucleotide primers specific for eubacteria. The PCR product generated with the eubacterial primers was transferred to a charged nylon membrane and probed with digoxigenin‐labeled synthetic oligonucleotides specific for Actinobacillus actinomycetemcomitans, Bacteroides forsythus, Porphyromonas gingivalis, and Prevotella intermedia. Results: Eighty percent of the 50 endarterectomy specimens were positive in 1 or more of the PCR assays. Thirty‐eight percent were positive for HCMV and 18% percent were positive for C. pneumoniae. PCR assays for bacterial 16S rDNA also indicated the presence of bacteria in 72% of the surgical specimens. Subsequent hybridization of the bacterial 16S rDNA positive specimens with species‐specific oligonucleotide probes revealed that 44% of the 50 atheromas were positive for at least one of the target periodontal pathogens. Thirty percent of the surgical specimens were positive for B. forsythus, 26% were positive for P. gingivalis, 18% were positive for A. actinomycetemcomitans, and 14% were positive for P. intermedia. In the surgical specimens positive for periodontal pathogens, more than 1 species was most often detected. Thirteen (59%) of the 22 periodontal pathogen‐positive surgical specimens were positive for 2 or more of the target species. Conclusions: Periodontal pathogens are present in atherosclerotic plaques where, like other infectious microorganisms such as C. pneumoniae, they may play a role in the development and progression of atherosclerosis leading to coronary vascular disease and other clinical sequelae. J Periodontol 2000;71:1554‐1560.